Atividade antidiabética, em modelo in vivo, da curcumina administrada em suspensão de iogurte na ausência e na presença de piperina - Arcaro Filho, Carlos Alberto [UNESP] (2014)
Previous studies showed that the treatment of diabetic rats with 90 mg of curcumin/kg body weight (bw) incorporated into yoghurt, for 31 days, improved several physiological and biochemical parameters altered in diabetes, compared to diabetic animals treated only with water or yoghurt. However, the low bioavailability of curcumin has stimulated the research of alternatives to improve its pharmacological effect. It has also been shown that piperine promotes an increase in the bioavailability of certain drugs when co-administered orally, including curcumin. The aim of this study was to investigate the antidiabetic and antioxidant activities of curcumin (90 mg/kg bw) alone or in combination with piperine (20 or 40 mg/kg bw) incorporated into yoghurt in diabetic rats induced by streptozotocin (STZ). Male rats (10 animals/group) under estreptozotocin diabetes model were orally treated for 45 days with: yoghurt (DYOG); insulin (4U/day, DINS, subcutaneously); 90 mg/kg curcumin incorporated into yoghurt (DC90), 20 or 40 mg/kg piperine (DP20 and DP40, respectively) associations of 90 mg of curcumin/kg bw and 20 or 40 mg of piperine/kg bw (DC90P20 and DC90P40, respectively) and The physiological parameters: body weight, food and water intake and urinary volume, and the biochemical parameters: glycemia, glycosuria, proteinuria and urinary urea were analyzed weekly, while the parameters related to lipid profile (triglycerides, total cholesterol and HDL-cholesterol) and liver function (ALT, AST and ALP) were analyzed at every 15 days. After euthanasia, it were removed and weighed the skeletal muscles soleus and extensor digitorum longus (EDL) and the epididymal and retroperitoneal white adipose tissues; liver was also removed to determine the activity of antioxidant enzymes and the levels of oxidative stress biomarkers. The treatment of diabetic rats with curcumin incorporated into yoghurt improved all parameters related to this experimental model of ...